2002
DOI: 10.1016/s1010-7940(02)00097-0
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoabdominal or descending aortic aneurysm repair after preoperative demonstration of the Adamkiewicz artery by magnetic resonance angiography☆

Abstract: Preoperative detection of the ARM is possible by MRA and is very useful for reducing the incidence of ischemic injury of the spinal cord and for reducing the time of an operation for repair of an aneurysm of the thoracoabdominal or descending aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…One possible cause of this variance is that diagnostic criteria were not identical among the studies. Multiphase dynamic imaging was performed by using MR imaging, [13][14][15][16] whereas single-phase imaging was performed by using CT. [19][20][21]24 We believe that multiphase imaging can improve the precision of AKA diagnosis. The present study showed that the detection rates of IACTA were better than those of IVCTA when using the same scan variables, contrast dose, injection rate, and diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible cause of this variance is that diagnostic criteria were not identical among the studies. Multiphase dynamic imaging was performed by using MR imaging, [13][14][15][16] whereas single-phase imaging was performed by using CT. [19][20][21]24 We believe that multiphase imaging can improve the precision of AKA diagnosis. The present study showed that the detection rates of IACTA were better than those of IVCTA when using the same scan variables, contrast dose, injection rate, and diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] However, selective angiography is time consuming, and complications including spinal cord injury can develop. 10,11 Recently, MR angiography (MRA) [13][14][15][16][17][18] and CT angiography (CTA) [17][18][19][20][21] have been used to visualize the AKA less invasively with reported detection rates of 67%-93% and 68%-90%, respectively. However, these rates could be further improved.…”
mentioning
confidence: 99%
“…4,5,[10][11][12][13] The use of these imaging techniques for preoperative analysis and surgical planning enables selective reconstruction of the feeding radiculomedullary artery. 4,5,14 However, it is di‹cult to reconstruct the artery of Adamkiewicz itself because of its small size (about 0.5 mm in diameter) and its branching from the intercostal/lumbar artery at the intervertebral foramen. Therefore, in the surgical approach, 2 methods are used to maintain the blood ‰ow to the artery of Adamkiewicz.…”
Section: Discussionmentioning
confidence: 99%
“…8 No. 4,2009 tors that might aŠect the branching level diŠerence: aortic elongation, decreasing vertebral height, vascular formative anomalies, and collateral supply. In our case series, there was no evidence of vertebral compression nor vascular formative anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation